القيم الفلسفية في كتاب الأدب الصغير والكبير لابن المقفع: Philosophical Values in Ibn Al-Muqaffa’s Kitab Al-Adab Al-Shagir and Al-Adab Al-Kabir - Kholil, Ahmad; Ainin, Moh; Faisol, M; Hasanah, Ummi; Wirmansyah, Aulia Fadhila (Jurnal Adabiyah, 2025)
This research aims to identify and to analyze the philosophical values contained in Ibn al-Muqaffa’s Kitab al-Adab al-Shagir and al-Adab al-Kabir. The main focus of this research is to explore how moral philosophy or ethical concepts are reflected in these two literary works and their relation to divine values, cosmology and humanism. This research is a literature study using a qualitative-descriptive analysis method. The primary data sources are texts from these two works as primary sources, as well as books and other references discussing philosophy and literature as secondary sources. The qualitative-descriptive method is used to systematically and deeply elaborate the data. The approach employed is content analysis with a philosophical perspective. This analysis is based on two ways of understanding: first, understanding the content within literary works and second, understanding communication as an interaction between the works and the readers. The findings of this research indicate that the philosophical values in Kitab al-Adab al-Shagir and al-Adab al-Kabir are related to the teachings of moral philosophy, encompassing God as the source of all existence, the universe as a reflection of God's existence and humans as beings possessing freedom and moral responsibility. الملخص يهدف هذا البحث إلى تحديد وتحليل القيم الفلسفية الواردة في كتاب "الأدب الصغير" و"الأدب الكبير" لابن المقفع. ويركز البحث بشكل رئيسي على استكشاف كيفية انعكاس مفاهيم الفلسفة الأخلاقية أو القيمية في هذين الكتابين، وعلاقتها بالقيم الإلهية والكونية والإنسانية.يُعَدُّ هذا البحث دراسة مكتبية تعتمد على منهج التحليل الوصفي النوعي. تستند مصادر البيانات الأساسية إلى نصوص الكتابين كمصدر أولي، بالإضافة إلى الكتب والمراجع الأخرى التي تتناول الفلسفة والأدب كمصادر ثانوية. ويُستخدم المنهج الوصفي النوعي لتحليل البيانات بشكل منهجي وعميق.المنهج المستخدم هو تحليل المحتوى من منظور فلسفي، حيث يعتمد هذا التحليل على طريقتين في الفهم: الأولى، فهم محتوى الأعمال الأدبية، والثانية، فهم عملية التواصل باعتبارها تفاعلاً بين العمل الأدبي والقارئ. وتشير نتائج البحث إلى أن القيم الفلسفية في "كتاب الأدب الصغير" و"الأدب الكبير" ترتبط بتعاليم الفلسفة الأخلاقية، والتي تشمل الله باعتباره مصدر الوجود، والكون باعتباره انعكاساً لوجود الله، والإنسان باعتباره كائناً يمتلك الحرية والمسؤولية Abstrak Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis nilai-nilai filosofis yang terkandung dalam Kitab al-Adab al-Shagir dan al-Adab al-Kabir karya Ibnu al-Muqaffa‘. Fokus utama penelitian ini adalah menggali konsep-konsep filsafat moral atau etika yang tercermin dalam kedua kitab tersebut serta keterkaitannya dengan nilai-nilai ketuhanan, kosmologi, dan humanisme. Penelitian ini merupakan studi pustaka dengan metode analisis kualitatif-deskriptif. Sumber data utama berasal dari teks dalam kedua kitab tersebut sebagai sumber primer, serta buku-buku dan referensi lain yang membahas filsafat dan sastra sebagai sumber sekunder. Metode kualitatif-deskriptif digunakan untuk menguraikan data secara sistematis dan mendalam. Pendekatan yang digunakan adalah analisis isi dengan perspektif filsafat. Analisis ini didasarkan pada dua cara pemahaman: pertama, pemahaman terhadap isi karya sastra, dan kedua, pemahaman komunikasi yang terjadi antara karya dan pembaca. Hasil penelitian ini menunjukkan bahwa nilai-nilai filsafat dalam kedua kitab tersebut berkaitan dengan ajaran filsafat moral yang mencakup Tuhan sebagai sumber segala wujud, alam semesta sebagai refleksi eksistensi Tuhan, dan manusia sebagai makhluk yang memiliki kebebasan serta tanggung jawab moral.